KAMPUNG BATIK DIGITAL BERBASIS VIRTUAL TOUR SEBAGAI WADAH PROMOSI BATIK KOTA PEKALONGAN DI ERA INDUSTRI 4.0 (Studi Kasus: Kampung Batik Banyurip) - Susanto, Eko Budi; Wijonarko, Rizqi; Purwanto, Edi; Binabar, Sattriedi Wahyu (JURNAL LITBANG KOTA PEKALONGAN, 2019)
The promotion of batik products in the Pekalongan batik city needs to be carried out so that it can be better known to the community, but is constrained by the limited working hours available. On the other hand President Joko Widodo stressed that the need to create a virtual trade exhibition, so that buyers can interact without the need to wait for an exhibition or are constrained by time. To respond to the appeal of Mr. Joko Widodo, through the development of virtual reality tenology which has also given birth to virtual tour innovations, a virtual tour village based on virtual tour will be built, so that batik artisans will have more time to promote their products, as well as visitors / consumers who have not had time to come to the batik village, will still be able to see the atmosphere of the existing batik village by accessing the digital batik village application of Pekalongan batik city based on virtual tour, and keep interacting with Pekalongan batik craftsmen, whenever and wherever. The application of this research will have a positive impact on several parties, namely: 1) batik artisans, 2) visitors / consumers, and 3) Pekalongan city government. The existence of digital batik villages based on virtual tours will be a new breakthrough / new paradigm in creating and managing batik villages so that they can be visited from anywhere and anytime. Keywords: Batik Village, Digital, Virtual Tour